Russian and Chinese Students: Proactive Behaviour and Economic Activity Characteristics - Olga Mihailova; Elizaveta S. Farennikova (International Journal of Cognitive Research in Science, Engineering and Education)
The relevance of the study of young people’s economic behaviour features is beyond doubt, because the younger generation is the future social capital and economically active population of any country. The purpose of the presented study was to identify the specifics of proactive behaviour and economic activity (as indicators of economic behaviour), their demonstration and interrelation among Russian and Chinese students. One hundred and two Russian and Chinese students took part in the study. The following techniques were used: 1) “Proactive behaviour” Methodology by A.I. Yerzin; 2) “Questionnaire of economic activity” by E.V. Zabelina and Yu.V. Chestyunina; 3) “Questionnaire of subjective economic well-being” by V.A. Khashchenko; 4) “Monetary attitudes” Questionnaire by B. Klonts and T. Klonts adapted by D.A. Bayazitova and T.A. Lapshova. Mathematical analysis methods: Mann-Whitney U-test and Spearman’s rank correlation coefficient. The results showed that the indicators of proactive behaviour demonstrated by the Russian students were higher than those demonstrated by Chinese students. The cognitive economic activity indicators were higher among the Chinese students. The Chinese students appeared to be more vigilant and careful with finances. The Russian students showed better results in experiencing a lack of financial resources. The specificity of economic behavior in Russian students is manifested through internal behavioral determination and constructive proactivity. Chinese students demonstrate cognitive economic activity and responsibility in relation to money. Based on the acquired results, the paper presents recommendations for the Russian and Chinese students’ economic behaviour development and correction.